1987
DOI: 10.1093/genetics/116.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Affecting Expression of the rosy Locus in Drosophila melanogaster

Abstract: The rosy locus in Drosophila melanogaster codes for the enzyme xanthine dehydrogenase (XDH). Previous studies defined a "control element" near the 5′ end of the gene, where variant sites affected the amount of rosy mRNA and protein produced. We have determined the DNA sequence of this region from both genomic and cDNA clones, and from the ry  +10 underproducer strain. This variant strain had many sequence differences, so that the site of the regulatory change could not be fixed. A mutagenesis was also undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recent work has shown the bovine milk oxidase probably occurs physiologically as the dehydrogenase and that the change in flavin reactivity (O 2 versus NAD + ) is a result of thiol oxidation and/or proteolysis that occurs during purification (Hunt & Massey, 1992). In addition to the extensive literature on the properties and reactivities of the bound cofactors, the gene sequences and deduced amino acid sequences of enzymes from at least seven species (all eukaryotes, including the human) have been determined [human liver, Ichida et al (1993) and Xu et al (1994); rat liver, Amaya et al (1990); mouse liver, Terao et al (1992); chicken liver, Sato et al (1995); Aspergillus nidulans, Glatigny and Scazzocchio (1995); Drosophila melanogaster, Lee et al (1987) and Keith et al (1987); Calliphora Vicina, Houde et al (1989)]. These studies have suggested specific domains for cofactor localization which, in the case of the chicken enzyme, has been further documented by limited proteolysis experiments (Sato et al, 1995).…”
mentioning
confidence: 99%
“…Recent work has shown the bovine milk oxidase probably occurs physiologically as the dehydrogenase and that the change in flavin reactivity (O 2 versus NAD + ) is a result of thiol oxidation and/or proteolysis that occurs during purification (Hunt & Massey, 1992). In addition to the extensive literature on the properties and reactivities of the bound cofactors, the gene sequences and deduced amino acid sequences of enzymes from at least seven species (all eukaryotes, including the human) have been determined [human liver, Ichida et al (1993) and Xu et al (1994); rat liver, Amaya et al (1990); mouse liver, Terao et al (1992); chicken liver, Sato et al (1995); Aspergillus nidulans, Glatigny and Scazzocchio (1995); Drosophila melanogaster, Lee et al (1987) and Keith et al (1987); Calliphora Vicina, Houde et al (1989)]. These studies have suggested specific domains for cofactor localization which, in the case of the chicken enzyme, has been further documented by limited proteolysis experiments (Sato et al, 1995).…”
mentioning
confidence: 99%
“…The sequences of the 7.3-kb Hind111 fragments from the ry+' and ry+5 background alleles were also determined from four overlapping PCR generated fragments (ry+O), or from a full length HindIII clone derived from a bacteriophage lambda library (ry+'). Parts of these sequences are published (LEE et al 1987;CURTIS et al 1989), and the full sequences will be presented elsewhere.…”
Section: Isolation Of Recombinantsmentioning
confidence: 99%
“…The Xdh gene (rosy in Drosophila melanogaster) , which codes for xanthine dehydrogenase, is one of the longest genes sequenced both in D. mdanogaster (KEITH et al 1987;LEE et al 1987) and D. pseudoobscura (RILEY 1989).…”
mentioning
confidence: 99%